ESTADO DE LA TELEFONÍA EN EL PERÚ AL AÑO 2005 - Hidalgo Sánchez, Augusto (2006)
The telephonic service in Peru has grown from 3.4 to 28.8 lines per one hundred people in the period from 1994 – 2005. This growing taked place in the setting of privatization norms of the public services occured in 1994, in middle of the international tendencies of incorporating high speed transmission technologies, cost reductions and the suddenly increase in the frecuency of international calls. Nevertheless, this phenomenon is not exclusive of Perú, but covers all Latin America. In addition, Perú has the least regional telephonic development, scene where Chile stands out with a density of 66 telephones per one hundred people. Internally, there is a highly telephonic service concentration in the city of Lima with a density of 56 lines per one hundred habitants, while regions in the highlands and jungle the density are 1.6 lines per one hundred habitants. Facing this scene is necessary to notice Peruvian concession model and also the small State activity in promoting this service in the poorest zones of the country.